Theorizing institutional change and governance in European responses to the Covid-19 pandemic. Issue 8 (16th November 2020) - Schmidt, Vivien A.
ABSTRACT: After initial responses that appeared to be a disappointing replay of previous crises, EU governance in the Covid-19 crisis may very well result in paradigmatic change toward deeper European integration in some areas, incremental change in others, or even reversal toward dis-integration in yet others. It is therefore important to evaluate what changed in terms of policies and who governed in what ways during the pandemic. This concluding article does so by building on the other articles in this SI. It first sheds light on policy change during the crisis using a historical institutionalist framework, then on governance by asking which EU actors, intergovernmental or supranational, drove integration and how, using rational choice and discursive institutionalist frameworks. Finally, it also considers the effects of post-functionalist politicization to elucidate the more positive dynamics of interaction among EU actors during the pandemic, in contrast to the Eurozone.